Effects of salinity on reproductive characteristics and embryo quality of Eriocheir sinensis. (11th July 2022) - Huang, Xiaorong; He, Lulu; Tan, Ru; Feng, Guangpeng; Geng, Zhi; Zhao, Feng; Zhang, Tao; Zhuang, Ping
Abstract: In order to find out the effects of salinity on the reproductive characteristics and embryo quality of female E. sinensis broodstock, the mating and spawning experiments of broodstock under different salinities (3, 6, 9, 12, 15, 18, and 21 ppt) were conducted, and each treatment had three replicate tanks with five males and 10 females stocked in each tank. The reproductive characteristics of broodstock, such as mating and spawning rate, egg production, reproductive index and fecundity, and the egg diameter, weight, biochemical composition and fatty acid composition of embryos were analysed. The results showed that female crabs can mate but did not spawn at salinity 3 ppt, and the lowest salinity for spawning was 6 ppt. When the salinity was 18 ppt, the egg production, reproductive index and fecundity of the broodstock reached the highest. The embryo diameter was the largest at salinity 6 ppt, which was significantly higher than that in other groups ( p  < 0.05). When the salinity was 12 ppt, the wet weight and dry weight of a single embryo were the highest. With the increase in salinity, the contents of crude protein, total lipid and moisture in the embryo of E. sinensis increased first and then decreased. When the salinity was 15 ppt, the contents of crude protein, total lipid and ash in embryos reached the highest. At salinity 21 ppt, the total contents of saturated fatty acids (SFA) and polyunsaturated fatty acids (PUFA) were the highest, and there were significant differences with other groups ( p  < 0.05). The total amount of MUFA was the highest at salinity 12 ppt. The results provided a theoretical basis and reference for artificial culture and breeding of E. sinensis .